Une observation clinique d’orientation psychanalytique des pratiques enseignantes - Philippe Chaussecourte (Recherches en Éducation)
This paper concerns what has been termed the clinical observation of teaching practices. It will situate this approach from the epistemological standpoint within the general context of observation practices in the human sciences. This specific orientation falls within the domain of the clinical, psychoanalytically oriented approach in Education Science. Having briefly resumed certain focal aspects of this approach, the paper will define a number of basic points on the subject of observation, notably taking care to evoke the notion of objective perception. It will then put the approach into perspective by evoking a selection of references that are indispensable for defining the connection of clinical observation to psychoanalysis. Having done this, it will briefly define the sense in which the work involves direct observation, and the use made in it of the term "practises." The debate on the relation of observation and psychoanalysis will then be evoked, and this will open the way to the last part of the paper which proposes an "ultra-clinical", psychoanalytically-oriented approach to teaching practises. References will be made throughout the article to E. Bick’s method for the observation of babies, one of its main sources of inspiration.